2022
DOI: 10.1088/2058-6272/ac78cd
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of stimulated growth effect using pulsed cold atmospheric plasma treatment on Ganoderma lucidum

Abstract: Cold atmospheric plasma (CAP) driven by pulsed high-voltage power has specific advantages in various fields, such as the growth promotion of edible fungi in plasma agriculture. Compared with other strains, Ganoderma lucidum has the significant advantage of high medicinal value, but the shortcomings of low yield, long growth cycle, and an uneven market quality. In this study, Ganoderma lucidum was treated with a CAP powered by a homemade pulsed high-voltage power supply. Three groups of Ganoderma lucidum were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The expansion of ARTP mutagenesis application in obtaining polysaccharideenhanced Ganoderma mutants was also demonstrated. 78 Zhang's group, 149 significantly increased the intracellular polysaccharide production and flavonoid content of Morus alba strains by ARTP mutagenesis. It was also noted that ARTP was used to increase polysaccharide production by increasing the molecular weight and in vitro macrophage activation activity in the Morus alba strain.…”
Section: Artp Mutagenesis Of Edible Fungimentioning
confidence: 99%
See 4 more Smart Citations
“…The expansion of ARTP mutagenesis application in obtaining polysaccharideenhanced Ganoderma mutants was also demonstrated. 78 Zhang's group, 149 significantly increased the intracellular polysaccharide production and flavonoid content of Morus alba strains by ARTP mutagenesis. It was also noted that ARTP was used to increase polysaccharide production by increasing the molecular weight and in vitro macrophage activation activity in the Morus alba strain.…”
Section: Artp Mutagenesis Of Edible Fungimentioning
confidence: 99%
“…[74][75][76] In recent years, an increasing number of researchers have found that sublethal effects on cells can be achieved by controlling the power and treatment time of ARTP, 11 and beyond a certain range, lethal effects can occur, thus extending the application of biological mutagenesis. 77,78 The different biological effects resulting from the interaction between ARTP and organisms are achieved through a series of complex reactive processes. Li et al, 25 introduced the genetic effect of atmospheric pressure helium RF plasma discharge in detail, and found that it was mainly some highly chemically reactive chemical species, such as hydroxyl radical (•OH), oxygen radical (•O), singlet oxygen ( 1 O 2 ), and nitric oxide (NO), which provided the feasibility for using ARTP to mutate organisms.…”
Section: Artp Mutagenesis Mechanismmentioning
confidence: 99%
See 3 more Smart Citations